Investigation on aerodynamic performance of horizontal axis wind turbine by setting micro-cylinder in front of the blade leading edge. (15th January 2018) - Wang, Ying; Li, Gaohui; Shen, Sheng; Huang, Diangui; Zheng, Zhongquan
Abstract: For NREL Phase VI horizontal axis wind turbine, a flow control method to suppress the flow separation by setting micro-cylinder in front of the blade leading edge is proposed, and the corresponding numerical simulation analysis for the aerodynamic performance of wind turbine is conducted. Firstly, the results predicted by simulation are confirmed experimentally. Under the same operating condition, the simulation and experimental results of low-speed shaft torque are compared, along with results from other studies. It can be found that the simulation results can accurately reflect the basic physical characteristics of flow field for NREL Phase VI wind turbine. Secondly, the influence of different diameters and positions of micro-cylinders on aerodynamic performance of wind turbine is discussed. Numerical results suggest that under different stall conditions, setting appropriate micro-cylinders in front of the blade leading edge can effectively suppress flow separation on wind turbine blades without increasing the load of wind turbine. Moreover, under different wind speeds, micro-cylinders with different diameters and positions have various impacts on aerodynamic performance of wind turbine. Through numerical calculation, the blade torque can maximally have an increase of 27.3% by setting a micro-cylinder with proper diameter and position in front of the blade leading edge. Highlights: Micro-cylinder is set in front of the blade leading edge to increase blade torque. Simulation results are compared with experimental results for validation. Influence of diameters and positions of micro-cylinders are discussed numerically. Blade torque can be improved obviously with proper setting of micro-cylinders. Flow separation can be suppressed effectively by setting appropriate micro-cylinders.